Fortalecimiento del espíritu creativo a través del arte plástico con los niños y niñas de 4 a 5 años - Herrera Herrera, Carla Elizabeth (2016)
This research was based on a problem in the Educational Unit Poalo "Garcia Moreno" during the academic period 2015-2016; in the same participated the educational community, taking into account that the research objective is to strengthen the creative spirit through the arts with a total of ten boys and ten girls in education, Cynthia MacGregor mentions that creativity comes in all and each of the children, promote the development of creativity it is essential for them, as this significant capability helps to express themselves, it develops their abstract, it will be essential to solving problems and to relate better others throughout their life. Albertina Moya said that the cultivation of the fine arts for the child, it means that they want to know and manipulate, when children draw, shape dough, or any other material which is transformed into an expression, they are developing plastic arts. It is important for the development of infants allow the spaces, resources, freedom to express themselves through creativity and the arts taking into account a quanti - qualitative methodology for a better result.